Effectiveness of agricultural water management technologies on rainfed cereals crop yield and runoff in semi-arid catchment: a meta-analysis. Issue 4 (3rd September 2018) - Magombeyi, M. S.; Taigbenu, A. E.; Barron, J.
ABSTRACT: Multiple agricultural water management (AWM) technologies are being promoted worldwide in rainfed agro-ecological production systems, such as the Limpopo River Basin, to close the yield gap, enhance food security and reduce poverty, but evidences on yield gains and environmental impacts are varied. This paper conducts a review of the performance of AWM technologies against conventional farmer practices to produce adequate evidence on cereal yield and field runoff changes. With the interrogation of literature from 1980 to 2013 using seven AWM groupings, enough evidence was found that AWM technologies can deliver substantial benefits of increased crop yield and water productivity with reduced environmental impacts. Using random effects model, the standardized mean difference (SMD) of yield between AWM and control was 0.27, while SMD of water productivity was 0.46, indicating the effectiveness of the technologies (SMD > 0). Subgroup analyses showed greatest yield responses on silty-clay-loam, clay-loam and sandy soils compared to clay and loam-sandy soils, and higher yield increase under low rainfall regime (200–500 mm) than under high rainfall regime (500–800 mm). Large yield change variations for different AWM technologies present a huge opportunity for meeting the existing yield gaps and enhancing coping capacity in dry years and under climate change.